2018
DOI: 10.1130/g39868.1
|View full text |Cite
|
Sign up to set email alerts
|

Deep-basin evidence resolves a 50-year-old debate and demonstrates synchronous onset of Messinian evaporite deposition in a non-desiccated Mediterranean

Abstract: The Messinian salinity crisis (MSC) is perceived as an environmental crisis governed by climatic and tectonic controls, affecting global oceans' salinity and shaping the Mediterranean Sea's biochemical composition. Recently drilled offshore wells in the Levant Basin retrieved a sedimentary record of the deep-basin Mediterranean MSC salt deposits and the underlying pre-evaporite unit. In this study, we have concentrated on the pre-evaporite interval and its transition into the overlying evaporites. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…During this catastrophic event, the Mediterranean basins experienced cyclic hypersaline conditions and deposition of a thick evaporite series. Evidence for partial or complete desiccation has been presented in a number of studies from the Mediterranean region (Ben-Gai et al, 2005;Druckman et al, 1995;Hsü et al, 1973;Ryan, 2008;Urgeles et al, 2011), while contesting studies doubt a sea-level drawdown of this magnitude (Gvirtzman et al, 2017;Lugli, Manzi, Roveri, & Schreiber, 2015;Meilijson et al, 2018;Roveri, Flecker et al, 2014a;Vasiliev et al, 2017). In the Levant Basin, the thickness of the Messinian evaporite sequence amounts to ca.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…During this catastrophic event, the Mediterranean basins experienced cyclic hypersaline conditions and deposition of a thick evaporite series. Evidence for partial or complete desiccation has been presented in a number of studies from the Mediterranean region (Ben-Gai et al, 2005;Druckman et al, 1995;Hsü et al, 1973;Ryan, 2008;Urgeles et al, 2011), while contesting studies doubt a sea-level drawdown of this magnitude (Gvirtzman et al, 2017;Lugli, Manzi, Roveri, & Schreiber, 2015;Meilijson et al, 2018;Roveri, Flecker et al, 2014a;Vasiliev et al, 2017). In the Levant Basin, the thickness of the Messinian evaporite sequence amounts to ca.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Their conclusions are supported by cross‐plots of seismic velocities, densities and Neutron porosities from six deep‐water industry wells. (b) Meilijson et al () concluded, utilizing well data and cuttings, that halite precipitation in the Levant basin was initiated around the onset the MSC phase 1, ca. 5.97 Ma.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly changing surface‐water paleoenvironments, leading to oligotypic assemblages, scarcity of calcareous nannofossils, and eventually to a‐planktonic zones in foraminifera record, may in part be explained by periodically enhanced salinity (Kouwenhoven & van der Zwaan, ). Finally, astronomical tuning of the pre‐evaporitic succession showed that the MSC onset was synchronous throughout the Mediterranean (e.g., Krijgsman et al, ; Manzi et al, ; Meilijson et al, ). However, the salinity changes accompanying the way into the MSC are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the offshore record is mainly known through geophysical data; DSDP and ODP cores have recovered on average only a few tens of metres of the top of the deep offshore salt giant (see Lugli, Manzi, Roveri, & Schreiber, ; Roveri, Lugli, Manzi, Gennari, & Schreiber, ). Recently, well logs and cuttings made available by oil companies allowed dating of the onset of MSC and of evaporite deposition (Manzi et al, ; Melijson et al, ), and the top of the main evaporitic body in the Eastern Mediterranean (Gvirtzman et al, ). Despite these important results, on‐average low seismic resolution and scarce core data still hamper the full understanding of Messinian events, thus fuelling lively controversies and several contrasting scenarios (Roveri, Flecker, et al, ).…”
Section: Introductionmentioning
confidence: 99%